MODEL PENILAIAN KINERJA DOSEN MENGGUNAKAN METODE SAW (STUDI KASUS STIKES YATSI TANGERANG) - Muhamad Yusup; Diah Aryani; Laurentius Andriyanto (Journal of Innovation And Future Technology (IFTECH), 2019)
Every certain period of time, the STIKes Yatsi Tangerang carry out a performance evaluation oflecturers to assess the performance of lecturers, determine the best lecturers, and improve the quality ofeducation. Because lecturers are an important component in leading quality universities. The existence ofquality educators is an absolute requirement for the presence of quality education systems and practices. Theabsence of a system that can assist in assessing the performance of lecturers and the lack of competencystandards for evaluating lecturer performance is a problem that exists in the running system at STIKes Yatsi inassessing the performance of lecturers. To overcome this problem, a decision support system was designed toassist in the process of evaluating the performance of lecturers using the Simple Additive Weighting (SAW)method. The SAW method is the simplest and most widely used method. This method is also the easiest to use,because it has an algorithm that is not too complicated. The SAW method is often also known as the weightedsum method. The basic concept of the SAW method is to find a weighted sum of performance ratings on eachalternative on all attributes. In this study the system design tools use the Unified Modeling Language (UML).The final result of this research is that the SAW method is expected to be able to overcome the problems inevaluating the performance of lecturers at the STIKes Yatsi Tangerang.